Cultural adaptation and academic success of international students in Beijing: The role of social integration - Qamar, Fatima (Journal of International Students, 2026)
International students in China face academic and cultural challenges that affect their educational outcomes. This study investigates how cultural adaptation and social integration influence academic performance among international students in Beijing. The purpose is to identify whether social integration mediates the relationship between cultural adjustment and student success. A quantitative, cross-sectional survey was conducted with 350 international students from six universities, using validated scales to assess adaptation, integration, and academic performance. The data were analyzed using SPSS and Hayes’ PROCESS mediation models. The results show that cultural adaptation significantly predicts academic performance, with social integration mediating 64% of this effect. Students reported language barriers and limited support services as major challenges. These findings highlight the need for targeted interventions such as peer mentoring, discipline-specific language training, and faculty development in intercultural teaching. This study contributes practical recommendations for improving support systems and advancing inclusive practices in international higher education.